Can we break their silence? Exploring the causes of undergraduates’ reluctance in speaking in english in an esl classroom - Shavindra Chandradasa (University of Jaffna, 2019)
This study objects to find out the causes which discourage undergraduates in speaking in English. Psychological, linguistic and cultural factors were considered as the key components in conducting the research. Based on the related literature it was hypothesized that there was a negative relationship between psychological, linguistic and cultural factors and speaking in English. For the study 50 students were randomly selected from 108 students who followed the credit course unit, ‘Speech and Communication Skills’ in the University of Ruhuna, Faculty of Science and they were given a questionnaire. As the discourse aspect of the study is also important 10 students and five language teachers who voluntarily participated were also interviewed. The data was qualitatively and quantitatively analyzed. It was quantitatively analyzed using SPSS. The results revealed that all the three components negatively influence students in speaking in English. Nevertheless, in the context, psychological factors appeared to exercise more negative influence on the students than the other two factors. Among psychological factors lack of confidence was the biggest issue faced by most of the students. Regarding linguistic factors, lack of vocabulary and dealing with university subculture peer influence appeared to disappoint the students more in speaking in English. As possible solutions to overcome these issues, the teachers have to be more creative, passionate and need to create a very friendly classroom atmosphere. Not only that but also the students too should stop underestimating their capacity when they speak in English. Even the university also needs to start setting a good background for language learners introducing new speech course units and sound language bodies.
Keywords: Undergraduates; psychological factors; linguistic; university subculture; passionate